EFEKTIFITAS MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA SMP NEGERI 2 SIGLI - Mastura, Winta; Razi, Zulfa (EDUTECH CONSULTANT, 2018)
The problem-based learning model is one of the learning approaches used to stimulate high-level thinking of students in real-world-oriented situations, including how to learn. The formulation of the problem in this research is whether the application of problem-based learning model can improve student activity on learning mathematics? Is the application of problem-based learning model can improve student learning outcomes in learning mathematics? How is the effectiveness of teacher management skills in learning mathematics with problem-based learning model? This study aims to determine the effectiveness of problem-based learning model of learning outcomes, student activities and the ability of teachers in managing learning. This research belongs to qualitative and quantitative descriptive research. Based on the results of student learning outcomes as much as 68% meet the KKM, the percentage is classified as high category. Student activity, its effectiveness belong to active category. The ability of teachers in managing learning using problem-based learning model on the subject of algebraic operations in RPP I obtained an average of 3.43 while in RPP II of 3.62 in general, including the active category.